A method and system for evaluating the suitability of solid waste-based cementitious materials
By mixing solid waste materials with alkali excitation solution and conducting specific tests, the alkali excitation activity, ion transport resistance and gas transport resistance of solid waste-based gelling materials are solved, and the problem of long test time and inaccurate results in the prior art is solved, and a rapid and accurate evaluation of the suitability of solid waste-based gelling materials is achieved.
Patent Information
- Application Number
- CN202411930971.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The prior art is difficult to effectively evaluate the applicability of solid waste-based gelling materials, especially in terms of alkali activation activity, ion transport resistance in wet conditions and gas transport resistance in dry conditions. The test time is long and the results are not accurate enough.
By mixing solid waste material with alkali excitation solution, clean slurry tests are prepared, and conductivity and air pressure tests are performed under different operating conditions, and the air pressure-time curve is fitted with a specific function, the alkali excitation activity, ion transport resistance and gas transport resistance of solid waste-based gelling materials are evaluated.
It realizes rapid and accurate evaluation of solid waste-based gelling materials, shortens testing time, improves experimental efficiency, and provides accurate judgment on the applicable occasions of the materials.
Smart Images

Figure CN119355223B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste-based alkali-activated engineering materials, and in particular to a method and system for evaluating the applicability of solid waste-based gelling materials. Background Art
[0002] Steel slag is a by-product of oxygen top-blown converter steelmaking and arc steelmaking. my country produces about 120 million tons of steel slag each year during steelmaking, and the cumulative stockpile exceeds 1 billion tons. Due to many problems in terms of composition stability, impact on cement quality, thermal stability, harmful substance content and stability, the application of steel slag in cement production is limited. my country is the world's largest producer and consumer of ceramic products. According to incomplete statistics, my country produces more than 10 million tons of ceramic waste each year. A large amount of waste will be generated during the production, use, demolition and transformation of ceramics. If these wastes are not properly handled, they will become part of the abandoned ceramics. Sintered clay bricks are widely used masonry structural materials in my country. After urban renewal and demolition, these sintered clay bricks become construction waste. At present, their resource utilization technology is not yet mature. Slag is the waste slag produced when smelting pig iron. It is currently widely used as a mineral admixture. The above solid wastes are all siliceous and aluminum solid wastes, which may have certain alkali activation activity.
[0003] At present, the production technology of using solid wastes such as steel slag, waste ceramics, sintered clay bricks and slag for cementitious materials is still immature. Therefore, before using solid waste base to stimulate engineering materials, it is necessary to test their hydration activity. The methods for testing the hydration activity of waste can be summarized as hydration heat test method, free calcium determination method, activity index method, chemical analysis method, etc. The hydration heat method evaluates its activity by testing the heat generated by the mixing reaction of waste with water. This method is simple and easy to operate, and the test results are accurate and reliable, but the operation time is long and requires professional equipment and personnel. In addition, this method has a good test effect on high-activity wastes, but has certain limitations for the test of low-activity wastes. The free calcium determination method is to mix the waste with saturated lime water, and after a certain reaction time, the amount of unbound calcium hydroxide in the reaction solution is determined by titration, so as to calculate the content of free calcium in the slag powder and evaluate its activity. This method is simple to operate and the test time is short, but it is only suitable for the case where the waste contains a high amount of free calcium, and the test effect is not good for low-activity wastes. The activity index method is to mix waste with cement to prepare test pieces, and then cure them under the same conditions as the benchmark test pieces made of pure cement, and measure their compressive strength at specified ages (such as 7 days, 28 days, etc.). The activity index is equal to the ratio of the compressive strength of the test piece mixed with waste to the compressive strength of the benchmark test piece. This method can intuitively reflect the activity of waste in cement, but the test time is relatively long. The chemical analysis method determines the activity of slag by measuring specific chemical components in it, such as silicon dioxide, aluminum oxide, calcium oxide, manganese oxide, ferrous oxide, etc., and evaluates its hydration activity based on their relative proportions. This method overemphasizes the chemical composition and pays insufficient attention to the mineral composition, and in some cases it is quite different from the actual activity. Summary of the invention
[0004] In view of the above problems, the present invention provides a method and system for evaluating the applicability of solid waste-based cementitious materials. By evaluating the alkali activation activity, ion transmission resistance under humid conditions and gas transmission resistance under dry conditions of the solid waste-based cementitious materials, the application occasions and applicable conditions of the solid waste materials can be comprehensively and accurately determined. At the same time, the evaluation test time is greatly shortened.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] In a first aspect, the present invention provides a method for evaluating the applicability of solid waste-based cementitious materials, comprising the following steps:
[0007] S1, mixing the solid waste material with the alkaline stimulating solution to obtain a pure slurry specimen;
[0008] S2, curing the clean slurry specimen, testing the real-time conductivity, and drawing a conductivity-time curve; and then evaluating the alkali activation activity of the solid waste-based gelling material according to the information of the conductivity-time curve;
[0009] S3, under vacuum conditions, allowing the cured clean slurry specimen to precipitate a solution, and testing the conductivity of the precipitated solution to evaluate the ion transport resistance of the solid waste-based gelling material under humid conditions;
[0010] S4, placing the clean slurry specimen after the solution is precipitated into a closed environment with a pressure of ≤-80 kPa, and testing the real-time air pressure to draw an air pressure-time curve; then fitting the air pressure-time curve using formula 1 to obtain a k value, and using the k value to evaluate the gas transmission resistance of the solid waste-based cementitious material under dry conditions;
[0011] p=0.9-0.7e -kt Formula 1
[0012] In formula 1, p represents air pressure in atm; t represents time in min; k represents a constant;
[0013] S5, determining application scenarios of the solid waste material according to the evaluation results of the alkali excitation activity, the ion transmission resistance under wet conditions, and the gas transmission resistance under dry conditions.
[0014] Compared with the prior art, the method for evaluating the applicability of solid waste-based cementitious materials provided by the present invention is to mix the solid waste material to be tested with an alkali-excitation solution to obtain a pure slurry specimen, and evaluate the alkali-excitation activity by testing the conductivity-time curve information of the pure slurry specimen during the curing process; then, the conductivity of the precipitate of the pure slurry specimen after curing (the hardening process has basically ended) is tested, which can reflect the activity of the solid waste material reacting with water, and is used to evaluate the ion transmission resistance under humid conditions; then, based on the record of the change of air pressure over time in a closed environment, a specific function is used to fit the curve to evaluate the ability of air to enter the pores of the pure slurry specimen, and the k value in Formula 1 reflects the transmission rate of air in the pores, which is used to evaluate the gas transmission resistance under dry conditions; finally, the application occasions of the solid waste material are comprehensively judged through the alkali-excitation activity of the solid waste-based cementitious material, the ion transmission resistance under humid conditions, and the gas transmission resistance under dry conditions, and the applicable conditions are very accurate. In addition, the applicability evaluation method of solid waste-based cementitious materials provided by the present invention only needs to test the pure slurry specimens, and there is no need to make concrete specimens (generally requiring 28 days). The test time is greatly reduced, and the amount of experiments is greatly reduced. It is efficient and fast, with low testing costs, and has excellent market application value.
[0015] The present invention utilizes vacuum negative pressure technology to extract the solution inside the clean slurry specimen after curing. The vacuum negative pressure greatly reduces the content of carbon dioxide gas, thereby effectively avoiding the reaction between the precipitate and the carbon dioxide gas, resulting in inaccurate conductivity test. In the present invention, the evaluation method of gas transmission resistance is carried out after the precipitate is extracted. At this time, the moisture content in the clean slurry specimen is already very low. The transmission resistance test can reflect its internal porosity and its connectivity, and then obtain the intrinsic gas transmission resistance of the solid waste-based cementitious material. Since the gas transmission resistance is closely related to the moisture content in the material being tested, it is difficult to obtain the intrinsic gas transmission characteristics of the material being tested by other methods. The present invention has found through a large number of experiments that the image of the air pressure-time curve is closest to the function shown in Formula 1. When commercial software (such as Matlab, Origin) is used for numerical fitting, the fitting accuracy is relatively high.
[0016] The hydration heat method can only characterize the hydration rate of solid waste materials, and the free calcium determination method can only obtain the degree of reaction, but cannot characterize the transport performance of the material. Therefore, neither the hydration heat method nor the free calcium determination method can give the applicable occasions of the evaluated material (solid waste material). The applicability evaluation method of solid waste-based cementitious materials provided by the present invention can characterize the material transport performance under wet and dry conditions. Since the intrusion of harmful ions including chloride ions, sulfate ions, and magnesium ions depends on the transmission of water, the present invention can evaluate the durability of solid waste-based cementitious materials under wet conditions. In addition, alkali-excited materials generally have carbonization problems. The gas transmission test under dry conditions proposed by the present invention can reflect the transmission resistance of carbon dioxide gas in materials (finished products after gelling and curing, such as solid waste-based concrete).
[0017] Preferably, in S1, the solid waste material includes aluminosilicate solid waste material.
[0018] Further preferably, in S1, the solid waste material includes at least one of steel slag, ceramics, sintered clay bricks or slag.
[0019] Preferably, in S1, the alkaline excitation solution includes at least one of a sodium hydroxide aqueous solution, a sodium silicate aqueous solution, a potassium hydroxide aqueous solution or a sodium carbonate aqueous solution.
[0020] Preferably, in S1, the mass concentration of the alkaline excitation solution is 8% to 15%.
[0021] Further preferably, in S1, the modulus of sodium silicate is 1.5-1.8.
[0022] Preferably, in S1, the mass ratio of the solid waste material to the alkaline excitation solution is 100:(35~45).
[0023] The present invention can maximize the alkali excitation effect by limiting the concentration and addition amount of the alkali excitation solution, effectively control the dissolution heat and corrosiveness of the alkali excitation solution, and ensure safe and controllable operation; at the same time, the addition amount of water can be controlled to ensure that the hardening rate of the solid waste material is moderate, thereby improving the accuracy of the alkali excitation activity evaluation.
[0024] For example, in S1, the pure slurry specimen can be in block shape to facilitate subsequent evaluation.
[0025] Preferably, in S2, the curing temperature is 20°C to 65°C, the relative humidity of the curing is ≥90%, and the curing time is 6 days to 9 days. Further preferably, in S2, the curing temperature is 50°C to 65°C, the relative humidity of the curing is ≥95%, and the curing time is 6.5 days to 7.5 days.
[0026] The preferred curing conditions of the present invention can accelerate the hardening process of solid waste materials under high temperature conditions, reduce test time, and improve test efficiency; and can effectively prevent water loss under high humidity conditions, without adversely affecting the hardening process of solid waste materials, thereby ensuring the accuracy of the evaluation of its alkali activation activity.
[0027] Preferably, in S2, the specific step of evaluating the alkali-activated activity of the solid waste-based gelling material according to the information of the conductivity-time curve comprises:
[0028] Four characteristic points are marked on the conductivity-time curve: characteristic point zero represents the corresponding point at the beginning of the curing, characteristic point one represents the corresponding point at the peak value of the conductivity, characteristic point two represents the curve inflection point, and characteristic point three represents the corresponding point at the end of the curing; wherein the curve inflection point represents the point where the second-order derivative is 0;
[0029] On the conductivity-time curve, the conductivities corresponding to the characteristic points 0 to 3 are denoted as σ0, σ1, σ2 and σ3 respectively, and the area formed by the curve segment from the characteristic point 1 to the characteristic point 2 and the horizontal coordinate is denoted as S 12 The area formed by the curve segment from feature point 1 to feature point 3 and the horizontal coordinate is recorded as S 13 ;
[0030] The ion dissolution rate of the solid waste-based cementitious material is evaluated by using the value of σ1-σ0, and the ion dissolution rate of the solid waste-based cementitious material is evaluated by using S 13 / S 12 The value of is used to evaluate the degree of polymerization of the alkali-activated product of the solid waste-based gelling material; and the alkali-activated activity of the solid waste-based gelling material is determined according to the evaluation results of the ion dissolution rate and the degree of polymerization of the alkali-activated product.
[0031] In the present invention, the three points of characteristic point zero to characteristic point two are the three most important characteristic points on the conductivity-time curve, reflecting the shape of the curve; at the end of curing, the hardening process of the solid waste material has ended, and this point is taken as characteristic point three. When the solid waste material and the alkali-activated solution are mixed and cured at the beginning, the gelling component in the clean slurry specimen has not yet played a role, and the measured initial conductivity σ0 can be understood as the conductivity of the alkali-activated solution; if the solid waste material (gelling component) is easy to react with the alkali solution, it will dissolve more ions, and the measured conductivity will increase. Therefore, the present invention uses σ1-σ0 (the difference between the peak conductivity and the initial conductivity) to reflect the ion dissolution rate of the solid waste-based gelling material. After the solid waste material reacts with the alkali-activated solution, it still takes a certain amount of time to gradually harden and form a solid substance. Since the generated solid substance itself is not conductive, after the solid substance is formed, the conductivity measured is the conductivity of the pore solution in the pores that plays a conductive role. Therefore, for the pure slurry specimens with similar curve characteristics before the curve inflection point, the greater the conductivity measured after the curve inflection point, the greater the porosity of the generated solid material and the lower the degree of polymerization, and vice versa. 13 / S 12 It can reflect the degree of polymerization of alkali-activated products of solid waste-based cementitious materials.
[0032] Further preferably, in S2, the criteria for evaluating the ion dissolution rate of the solid waste-based gelling material using the value of σ1-σ0 include:
[0033] When σ1-σ0>60mS / m, the evaluation result is that the ion dissolution rate is high;
[0034] When σ1-σ0=30mS / m~60mS / m, the evaluation result is medium ion dissolution rate;
[0035] When σ1-σ0<30mS / m, the evaluation result is that the ion dissolution rate is low.
[0036] It should be noted that the unit of conductivity is millisiemens / meter, and correspondingly, the unit of σ1-σ0 is also millisiemens / meter, that is, mS / m.
[0037] Further preferably, in S2, S 13 / S 12 The criteria for evaluating the degree of polymerization of the alkali-activated product of the solid waste-based cementitious material include:
[0038] When S 13 / S 12 When <2.2, the evaluation result is that the degree of polymerization is high;
[0039] When S 13 / S 12=2.2~4, the evaluation result is medium degree of polymerization;
[0040] When S 13 / S 12 When >4, the evaluation result indicates that the degree of polymerization is low.
[0041] More preferably, in S2, the criteria for determining the alkali-activated activity of the solid waste-based gelling material include:
[0042] When the evaluation result of the ion dissolution rate is that the ion dissolution rate is high, and the evaluation result of the degree of polymerization of the base-excited product is that the degree of polymerization is high, the evaluation result of the base-excited activity is that the base-excited activity is high;
[0043] When the evaluation result of the ion dissolution rate is high, and the evaluation result of the degree of polymerization of the base-excited product is medium, the evaluation result of the base-excited activity is medium;
[0044] When the evaluation result of the ion dissolution rate is medium, and the evaluation result of the degree of polymerization of the base-excited product is high, the evaluation result of the base-excited activity is medium;
[0045] When the evaluation result of the ion dissolution rate is medium, and the evaluation result of the degree of polymerization of the base-excited product is medium, the evaluation result of the base-excited activity is medium;
[0046] As long as the evaluation result of the ion dissolution rate or the polymerization degree of the alkali-activated product is "low", the solid waste material does not have alkali-activated activity and has no value for use as a solid waste-based gelling material.
[0047] The present invention achieves accurate judgment on whether the solid waste material can be used as a solid waste-based gelling material and its alkali-activated activity after being used as a gelling material by further limiting the evaluation and judgment criteria of the ion dissolution rate, the polymerization degree of the alkali-activated product and the alkali-activated activity.
[0048] Preferably, in S3, the vacuum pressure is ≤-80 kPa, more preferably -90 kPa to -80 kPa.
[0049] For example, in S3, the vacuum condition is maintained unchanged, and after no solution is precipitated within 10 minutes, the conductivity of the precipitated solution is tested.
[0050] Further preferably, in S3, the conductivity of the precipitate is denoted as σ p , using σ3 / σ p The value of is used to evaluate the ion transport resistance of the solid waste-based cementitious material under humid conditions.
[0051] More preferably, in S3, σ3 / σ p The criteria for evaluating the ion transport resistance of the solid waste-based cementitious material under humid working conditions include:
[0052] When σ3 / σ p <10 -4 When , the evaluation result is that the ion transmission resistance is high;
[0053] When σ3 / σ p =1×10 -4 ~3×10 -4 When , the evaluation result is that the ion transmission resistance is medium;
[0054] When σ3 / σ p >3×10 -4 , the evaluation result is that the ion transmission resistance is low.
[0055] Preferably, in S4, when the air pressure of the closed environment is ≥ -10 kPa (more preferably -10 kPa to -3 kPa), the measurement of the real-time air pressure is stopped.
[0056] Preferably, in S4, the criteria for evaluating the gas transmission resistance of the solid waste-based gelling material under dry conditions using the k value include:
[0057] When k < 0.02, the evaluation result is that the gas transmission resistance is high;
[0058] When k = 0.02 ~ 0.06, the evaluation result is medium gas transmission resistance;
[0059] When k>0.06, the evaluation result is that the gas transmission resistance is low.
[0060] More preferably, in S5, the criteria for determining the application of the solid waste material include:
[0061] When the evaluation result of the alkali excitation activity is high alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is high ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is high gas transmission resistance, the application occasion of the solid waste material is a rapid repair occasion;
[0062] When the evaluation result of the alkali excitation activity is high alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is high ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is medium gas transmission resistance, the application occasion of the solid waste material is a rapid repair occasion that is often in contact with water;
[0063] When the evaluation result of the alkali excitation activity is high alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is medium ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is high gas transmission resistance, the application occasion of the solid waste material is a rapid repair occasion in a dry environment;
[0064] When the evaluation result of the alkali excitation activity is high alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based cementitious material under wet conditions is medium ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based cementitious material under dry conditions is medium gas transmission resistance, the application occasion of the solid waste material is a cast-in-place component with a waterproof coating or an anti-corrosion coating on the surface;
[0065] When the evaluation result of the alkali excitation activity is medium alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is high ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is high gas transmission resistance, the application occasion of the solid waste material is prefabricated component occasion;
[0066] When the evaluation result of the alkali excitation activity is medium alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is medium ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is high gas transmission resistance, the application occasion of the solid waste material is a prefabricated component occasion in a dry environment;
[0067] When the evaluation result of the alkali excitation activity is medium alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is high ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is medium gas transmission resistance, the application occasion of the solid waste material is a prefabricated component occasion that is often in contact with water;
[0068] When the evaluation result of the alkali excitation activity is medium alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is medium ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is medium gas transmission resistance, the application occasion of the solid waste material is a prefabricated component with a waterproof coating or an anti-corrosion coating on the surface;
[0069] As long as "low" appears in the evaluation result of the alkali activation activity, the ion transmission resistance under wet conditions, or the gas transmission resistance under dry conditions, the solid waste material has no value for use as a solid waste-based gelling material.
[0070] In the present invention, the requirements for cementitious materials in rapid repair applications are firstly fast strength development (i.e. high alkali activation activity), for example, road repair requires traffic to be open within a few hours; if it is resistant to aqueous solution intrusion (it is inevitable to contact water on the road) and does not effloresce (mainly due to carbon dioxide gas intrusion), it is more suitable for rapid road repair. If the strength development is slow (i.e. medium alkali activation activity), it can be used as a prefabricated component, because the prefabricated component factory has the conditions to adopt high temperature curing methods (such as steam curing) to increase the strength development speed; if it is resistant to ion intrusion (ions need to be invaded by solution), it can be used in occasions where it is often in contact with water; if it is resistant to gas intrusion but not resistant to solution intrusion, it can be used in occasions in dry environments. The preferred application scenarios of the present invention have made the best use of the strengths and avoided the weaknesses of the performance of solid waste materials, and the accuracy of the applicability evaluation results of solid waste-based cementitious materials is relatively high.
[0071] It should be noted that the cast-in-place component in the present invention is a professional term, which refers to a wall, a slab, a column or a beam.
[0072] In a second aspect, the present invention provides a system for evaluating the suitability of solid waste-based cementitious materials, including a conductivity test mold and a closed container; wherein:
[0073] The conductivity test mold is located in the upper middle part of the closed container and is used to place the clean slurry specimen and perform real-time conductivity test on the clean slurry specimen during the curing process;
[0074] An opening having the same size as the periphery of the conductivity test mold is provided in the middle and upper part of the sealed container for placing the conductivity test mold;
[0075] The sealed container is connected to a vacuum pump for constructing a vacuum environment and a sealed environment, so that the clean slurry specimen after curing precipitates a solution, and a real-time air pressure test is performed on the clean slurry specimen after the solution is precipitated;
[0076] A filter screen is provided at the bottom of the conductivity test mold for dripping the precipitate;
[0077] A groove is provided at the bottom of the sealed container, and the groove is located directly below the filter screen, and is used to hold the precipitate and test the conductivity of the precipitate.
[0078] The applicability evaluation system for solid waste-based cementitious materials provided by the present invention has a simple structure and low cost.
[0079] Preferably, the upper portion of the conductivity test mold is a hollow cylinder, the outer side of the cylinder is provided with threads, the opening of the sealed container corresponding to the outer side of the cylinder is also provided with threads, and the conductivity test mold and the sealed container are screwed together through the threads.
[0080] For example, in order to ensure airtightness, glass glue can be used for sealing.
[0081] Further preferably, two layers of parallel platinum mesh are provided in the cylinder, the diameter of the platinum mesh is the same as the inner diameter of the cylinder, the slurry specimen is placed between the two layers of platinum mesh, and the two layers of platinum mesh are respectively connected to the conductivity tester through leads.
[0082] Platinum is relatively inert and not easy to rust. Testing the conductivity of the pure slurry specimen through a platinum mesh will provide more accurate test results.
[0083] More preferably, the distance between the two layers of the platinum mesh is 20 mm to 30 mm, and the diameter of the platinum mesh is 50 mm to 80 mm.
[0084] More preferably, the mesh of the platinum mesh is a square with a side length of 1 mm to 3 mm, and the diameter of the platinum wire is 0.2 mm to 0.5 mm.
[0085] Preferably, the lower portion of the conductivity test mold is a hollow funnel-shaped cone, and the bottom of the funnel-shaped cone is the filter screen.
[0086] Further preferably, the diameter of the filter screen is 1 cm to 2 cm, and the mesh size of the filter screen is ≤ 0.5 mm (more preferably 0.2 mm to 0.5 mm).
[0087] For example, the mesh of the filter can be a square with a side length of ≤0.5 mm.
[0088] Preferably, a conductivity sensor is provided in the groove, and the conductivity sensor is connected to a conductivity tester via a lead wire.
[0089] Preferably, the volume of the sealed container is 800mL~1000mL.
[0090] For example, an opening is provided on the upper side of the sealed container, and the opening is connected to a vacuum pump; a barometer is provided on the side of the sealed container, and the barometer is connected to an air pressure measuring and recording device through a lead wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0091] Figure 1 It is a schematic structural diagram of the system for evaluating the suitability of solid waste-based cementitious materials in the present invention;
[0092] Figure 2 It is a schematic structural diagram of a conductivity test mold in the applicability evaluation system of solid waste-based gelling materials in the present invention;
[0093] Figure 1~Figure 2 In the figure, 1 represents a conductivity test mold, 11 represents a filter screen, 12 represents a hollow cylinder, 13 represents a platinum mesh, and 14 represents a hollow funnel-shaped cone;
[0094] 2 represents a closed container, 21 represents an opening, 22 represents a groove, 23 represents a conductivity sensor, 24 represents an opening, and 25 represents a barometer;
[0095] 3 represents a vacuum pump, 4 represents a conductivity tester, and 5 represents an air pressure measurement and recording device;
[0096] Figure 3 is a SEM image of the ceramic powder of the present invention;
[0097] Figure 4 is a particle size distribution diagram of the steel slag in the present invention;
[0098] Figure 5 The conductivity-time curve of Example 1 of the present invention;
[0099] Figure 6 is the air pressure-time curve of Example 1 of the present invention;
[0100] Figure 7 The conductivity-time curve of Example 2 of the present invention;
[0101] Figure 8 is the air pressure-time curve of Example 2 of the present invention;
[0102] Fig. 9 The conductivity-time curve of Example 3 of the present invention;
[0103] Fig.10 is the air pressure-time curve of Example 3 of the present invention;
[0104] Fig.11 It is a corresponding relationship diagram of σ1-σ0 of the embodiment in the verification test of the present invention and the 3d age compressive strength of the concrete of the application example;
[0105] Fig.12 S is the S of the embodiment in the verification test of the present invention. 13 / S 12 Corresponding relationship diagram with the 3d age compressive strength of concrete in the application example;
[0106] Fig.13 is σ3 / σ in the embodiment of the verification test of the present invention p A corresponding relationship diagram with the chloride ion migration coefficient of concrete in the application example;
[0107] Fig.14 It is a corresponding relationship diagram between the k value of the embodiment in the verification test of the present invention and the Figg air permeability index (FPI) of the concrete of the application example. DETAILED DESCRIPTION
[0108] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0109] See also Figure 1~Figure 2 The present invention provides a system for evaluating the suitability of solid waste-based cementitious materials, comprising a conductivity test mold 1 and a closed container 2; wherein:
[0110] The conductivity test mold 1 is located in the upper middle part of the closed container 2 and is used to place the clean slurry specimen and perform real-time conductivity test on the clean slurry specimen during the curing process;
[0111] An opening 21 having the same size as the periphery of the conductivity test mold 1 is provided in the middle and upper part of the sealed container 2 for placing the conductivity test mold 1;
[0112] The sealed container 2 is connected to a vacuum pump 3 for constructing a vacuum environment and a sealed environment, so that the clean slurry specimen after curing precipitates a solution, and performs a real-time air pressure test on the clean slurry specimen after the solution is precipitated;
[0113] The bottom of the conductivity test mold 1 is provided with a filter 11 for dripping the precipitate;
[0114] A groove 22 is provided at the bottom of the sealed container 2 . The groove 22 is located directly below the filter screen 11 and is used to hold the precipitate and test the conductivity of the precipitate.
[0115] In a preferred embodiment, the upper portion of the conductivity test mold 1 is a hollow cylinder 12, and the outer side of the cylinder 12 is provided with a thread ( Figure 1 and Figure 2 The opening 21 of the sealed container 2 is also provided with a thread (not shown) at a position corresponding to the outer side surface of the cylinder 12. Figure 1 and Figure 2 (not shown), the conductivity test mold 1 and the closed container 2 are screwed together through the thread.
[0116] In a preferred embodiment, two layers of parallel platinum mesh 13 are provided in the cylinder 12, the diameter of the platinum mesh 13 is the same as the inner diameter of the cylinder 12, the pure slurry specimen is placed between the two layers of the platinum mesh 13, and the two layers of the platinum mesh 13 are respectively connected to the conductivity tester 4 through leads.
[0117] In a preferred embodiment, the lower portion of the conductivity testing mold 1 is a hollow funnel-shaped cone 14 , and the bottom of the funnel-shaped cone 14 is the filter screen 11 .
[0118] In a preferred embodiment, a conductivity sensor 23 is provided in the groove 22 , and the conductivity sensor 23 is connected to the conductivity tester 4 via a lead wire.
[0119] In a preferred embodiment, an opening 24 is provided on the upper side of the sealed container 2, and the opening 24 is connected to the vacuum pump 3; a barometer 25 is provided on the side of the sealed container 2, and the barometer 25 is connected to the air pressure measuring and recording device 5 through a lead.
[0120] In the present invention, the conductivity tester adopts the Hioki IM3570 precision impedance analyzer, and the air pressure measurement and recording device adopts the Keyence AP-C30 gas pressure sensor.
[0121] It should be noted that the applicability evaluation method and system of solid waste-based cementitious materials provided by the present invention are theoretically applicable to all alkali-activated solid waste materials. However, in order to better illustrate through experimental data, the present invention only selects aluminosilicate solid waste materials such as ceramic powder, steel slag, sintered clay brick powder, slag and their combinations as examples.
[0122] The raw materials used in the present invention include:
[0123] Ceramic powder: Waste generated when a tile factory in Shijiazhuang City processes floor tiles, prepared by crushing and ball milling. Ceramic powder includes the following chemical components in mass percentage: SiO2 66.63%, MgO 0.85%, Na2O 1.01%, Fe2O3 0.94%, CaO 3.57%, Al2O3 19.01% and K2O 1.84%. The particle size distribution of ceramic powder is: the mass proportion of <10μm is 65.8%, the mass proportion of 10μm~20μm is 17.5%, the mass proportion of 20μm~30μm is 10.8%, and the mass proportion of >30μm is 17.5%. The electron microscope scanning image of ceramic powder is as follows Figure 3 shown.
[0124] Steel slag: A steel plant in Handan. Steel slag includes the following chemical components by mass percentage: SiO2 17.66%, MgO 5.86%, Na2O 0.20%, Fe2O3 22.70%, CaO 43.40%, Al2O3 5.61% and K2O 0.21%. The particle size distribution of steel slag is as follows: Figure 4 shown.
[0125] Sintered clay brick powder: Sintered clay brick is the main solid waste after the demolition of old masonry structures. It is taken from a landfill in Shijiazhuang and crushed and ground into powder. Sintered clay brick powder includes the following chemical components by mass percentage: SiO2 61.86%, MgO 2.08%, Na2O 1.61%, Fe2O3 6.51%, CaO 1.45%, Al2O3 21.38% and K2O 3.34%. The specific surface area of sintered clay brick powder is 460m 2 / kg.
[0126] Slag: Produced in Lincheng, Hebei. The slag includes the following chemical components by mass percentage: SiO2 22.28%, MgO 5.81%, Fe2O3 1.71%, CaO 52.60%, Al2O3 11.72% and SO3 1.40%. The specific surface area of the slag is 460m 2 / kg, particle size <60μm, D50 <10μm.
[0127] Water glass: Instant granular sodium silicate with a modulus of 1.6, produced by Qingdao Haiwan Chemical Co., Ltd.
[0128] Sand and stone: river sand, crushed limestone.
[0129] In order to better illustrate the present invention, further examples are given below.
[0130] Example 1
[0131] This embodiment provides a method for evaluating the suitability of solid waste-based cementitious materials, comprising the following steps:
[0132] S1, mix steel slag, ceramic powder and 10wt% sodium hydroxide aqueous solution, the mass ratio of steel slag, ceramic powder and sodium hydroxide aqueous solution is 50:50:41, pour into the conductivity test mold 1, vibrate and compact to obtain a pure slurry specimen.
[0133] S2, put the conductivity test mold 1 into the curing box at 60℃ and RH=95% for curing, and immediately start testing the real-time conductivity of the pure slurry specimen. The curing time is 7d, and the conductivity-time curve is drawn, as shown in Figure 5 shown.
[0134] Four characteristic points are marked on the conductivity-time curve: characteristic point zero represents the corresponding point at the beginning of curing (t=0), characteristic point one represents the corresponding point at the peak value of conductivity, characteristic point two represents the inflection point of the curve (the second-order derivative is 0), and characteristic point three represents the corresponding point at the end of curing; on the conductivity-time curve, the conductivity corresponding to characteristic point zero to characteristic point three is recorded as σ0, σ1, σ2 and σ3 respectively, and the curve segment area from characteristic point one to characteristic point two is recorded as S 12, the area of the curve segment from feature point 1 to feature point 3 is recorded as S 13 . After calculation, σ1-σ0=95-30=65mS / m, S 13 / S 12 =115.5 / 41.25=2.8.
[0135] The ion dissolution rate of solid waste-based cementitious materials was evaluated as “high” using the value of σ1-σ0, and the ion dissolution rate of solid waste-based cementitious materials was evaluated as “high” using the value of S 13 / S 12 The value of was used to evaluate the degree of polymerization of the alkali-activated products of the solid waste-based gelling material as “medium”; based on the evaluation results of the ion dissolution rate and the degree of polymerization of the alkali-activated products, the alkali-activated activity of the solid waste-based gelling material was determined to be “medium”.
[0136] S3, screw the conductivity test mold into the sealed container 2, turn on the vacuum pump 3 to make the air pressure of the sealed container 2 0.2 standard atmospheric pressure, and a solution will precipitate at the filter 11; keep the vacuum condition unchanged, and after no solution precipitates within 10 minutes, test the conductivity σ of the precipitate in the groove 22 p , after calculating σ3 / σ p =9.9×10 -3 / 61.88=1.6×10 -4 . Using σ3 / σ p The value of is used to evaluate the ion transport resistance of solid waste-based cementitious materials under wet conditions as “medium”.
[0137] S4, after completing the test of ion transmission resistance under humid working conditions, test the real-time air pressure of the sealed container 2 (ensure that the air pressure of the sealed container 2 is 0.2 standard atmospheric pressure when the test starts). When the air pressure of the sealed environment is greater than 0.9 standard atmospheric pressure, stop measuring the real-time air pressure and draw an air pressure-time curve, such as Figure 6 shown.
[0138] Then, the air pressure-time curve was fitted using Formula 1, and k = 0.018 was obtained. The k value was used to evaluate the gas transmission resistance of the solid waste-based cementitious material under dry conditions as "high".
[0139] p=0.9-0.7e -kt Formula 1
[0140] In formula 1, p represents air pressure, the unit is atm; t represents time, the unit is min; k represents a constant.
[0141] S5. Based on the evaluation results of alkali excitation activity, ion transmission resistance under humid conditions and gas transmission resistance under dry conditions, the application occasion of the solid waste material is determined to be "prefabricated components in dry environments".
[0142] Example 2
[0143] This embodiment provides a method for evaluating the suitability of solid waste-based cementitious materials, comprising the following steps:
[0144] S1, mixing steel slag, ceramic powder and 8wt% sodium hydroxide aqueous solution, the mass ratio of steel slag, ceramic powder and sodium hydroxide aqueous solution is 80:20:45, pouring into the conductivity test mold 1, vibrating and compacting to obtain a pure slurry specimen.
[0145] S2, put the conductivity test mold 1 into the curing box at 60℃ and RH=95% for curing, and immediately start testing the real-time conductivity of the pure slurry specimen. The curing time is 7d, and the conductivity-time curve is drawn, as shown in Figure 7 shown.
[0146] Four characteristic points are marked on the conductivity-time curve: characteristic point zero represents the corresponding point at the beginning of curing (t=0), characteristic point one represents the corresponding point at the peak value of conductivity, characteristic point two represents the inflection point of the curve (the second-order derivative is 0), and characteristic point three represents the corresponding point at the end of curing; on the conductivity-time curve, the conductivity corresponding to characteristic point zero to characteristic point three is recorded as σ0, σ1, σ2 and σ3 respectively, and the curve segment area from characteristic point one to characteristic point two is recorded as S 12 , the area of the curve segment from feature point 1 to feature point 3 is recorded as S 13 . After calculation, σ1-σ0=74-30=44mS / m, S 13 / S 12 =121.7 / 31.2=3.9.
[0147] The ion dissolution rate of solid waste-based cementitious materials was evaluated as “medium” using the value of σ1-σ0, and S 13 / S 12 The value of was used to evaluate the degree of polymerization of the alkali-activated products of the solid waste-based gelling material as “medium”; based on the evaluation results of the ion dissolution rate and the degree of polymerization of the alkali-activated products, the alkali-activated activity of the solid waste-based gelling material was determined to be “medium”.
[0148] S3, screw the conductivity test mold into the sealed container 2, turn on the vacuum pump 3 to make the air pressure of the sealed container 2 0.2 standard atmospheric pressure, and a solution will precipitate at the filter 11; keep the vacuum condition unchanged, and after no solution precipitates within 10 minutes, test the conductivity σ of the precipitate in the groove 22 p , after calculating σ3 / σ p =13×10 -3 / 144=0.9×10 -4 . Using σ3 / σ p The value of evaluates the ion transport resistance of solid waste-based cementitious materials under humid conditions as “high”.
[0149] S4, after completing the test of ion transmission resistance under humid working conditions, test the real-time air pressure of the sealed container 2 (ensure that the air pressure of the sealed container 2 is 0.2 standard atmospheric pressure when the test starts). When the air pressure of the sealed environment is greater than 0.9 standard atmospheric pressure, stop measuring the real-time air pressure and draw an air pressure-time curve, such as Figure 8 shown.
[0150] Then, the air pressure-time curve was fitted using Formula 1, and k = 0.022 was obtained. The k value was used to evaluate the gas transmission resistance of the solid waste-based cementitious material under dry conditions as "medium".
[0151] p=0.9-0.7e -kt Formula 1
[0152] In formula 1, p represents air pressure, the unit is atm; t represents time, the unit is min; k represents a constant.
[0153] S5. Based on the evaluation results of alkali excitation activity, ion transmission resistance under humid conditions and gas transmission resistance under dry conditions, the application occasion of solid waste materials is determined to be "prefabricated components that are frequently in contact with water."
[0154] Example 3
[0155] This embodiment provides a method for evaluating the suitability of solid waste-based cementitious materials, comprising the following steps:
[0156] S1, mixing sintered clay brick powder with 10wt% sodium hydroxide aqueous solution, the mass ratio of sintered clay brick powder to sodium hydroxide aqueous solution is 100:35, pouring into the conductivity test mold 1, vibrating and compacting to obtain a pure slurry specimen.
[0157] S2, put the conductivity test mold 1 into the curing box at 65℃ and RH=90% for curing, and immediately start testing the real-time conductivity of the pure slurry specimen. The curing time is 8d, and the conductivity-time curve is drawn, as shown in Fig. 9 shown.
[0158] Four characteristic points are marked on the conductivity-time curve: characteristic point zero represents the corresponding point at the beginning of curing (t=0), characteristic point one represents the corresponding point at the peak value of conductivity, characteristic point two represents the inflection point of the curve (the second-order derivative is 0), and characteristic point three represents the corresponding point at the end of curing; on the conductivity-time curve, the conductivity corresponding to characteristic point zero to characteristic point three is recorded as σ0, σ1, σ2 and σ3 respectively, and the curve segment area from characteristic point one to characteristic point two is recorded as S 12 , the area of the curve segment from feature point 1 to feature point 3 is recorded as S 13 . After calculation, σ1-σ0=111-30=81mS / m, S 13 / S 12=107 / 38.2=2.8.
[0159] The ion dissolution rate of solid waste-based cementitious materials was evaluated as “high” using the value of σ1-σ0, and the ion dissolution rate of solid waste-based cementitious materials was evaluated as “high” using the value of S 13 / S 12 The value of was used to evaluate the degree of polymerization of the alkali-activated products of the solid waste-based gelling material as “medium”; based on the evaluation results of the ion dissolution rate and the degree of polymerization of the alkali-activated products, the alkali-activated activity of the solid waste-based gelling material was determined to be “medium”.
[0160] S3, screw the conductivity test mold into the sealed container 2, turn on the vacuum pump 3 to make the air pressure of the sealed container 2 0.2 standard atmospheric pressure, and a solution will precipitate at the filter 11; keep the vacuum condition unchanged, and after no solution precipitates within 10 minutes, test the conductivity σ of the precipitate in the groove 22 p , after calculating σ3 / σ p =19.8×10 -3 / 215.2=0.92×10 -4 . Using σ3 / σ p The value of evaluates the ion transport resistance of solid waste-based cementitious materials under humid conditions as “high”.
[0161] S4, after completing the test of ion transmission resistance under humid working conditions, test the real-time air pressure of the sealed container 2 (ensure that the air pressure of the sealed container 2 is 0.2 standard atmospheric pressure when the test starts). When the air pressure of the sealed environment is greater than 0.9 standard atmospheric pressure, stop measuring the real-time air pressure and draw an air pressure-time curve, such as Fig.10 shown.
[0162] Then, the air pressure-time curve was fitted using Formula 1, and k = 0.016 was obtained. The k value was used to evaluate the gas transmission resistance of the solid waste-based cementitious material under dry conditions as "high".
[0163] p=0.9-0.7e -kt Formula 1
[0164] In formula 1, p represents air pressure, the unit is atm; t represents time, the unit is min; k represents a constant.
[0165] S5. According to the evaluation results of alkali excitation activity, ion transmission resistance under wet conditions and gas transmission resistance under dry conditions, the application occasion of the solid waste material is determined to be "prefabricated component".
[0166] Example 4
[0167] This embodiment provides a method for evaluating the suitability of solid waste-based cementitious materials, comprising the following steps:
[0168] S1, mixing ceramic powder with 15wt% sodium hydroxide aqueous solution, the mass ratio of ceramic powder to sodium hydroxide aqueous solution is 100:35, pouring into the conductivity test mold 1, vibrating and compacting to obtain a pure slurry specimen.
[0169] S2, put the conductivity test mold 1 into the curing box at 35℃ and RH=95% for curing, and immediately start testing the real-time conductivity of the clean slurry specimen. The curing time is 9d, and the conductivity-time curve is drawn. Mark 4 characteristic points on the conductivity-time curve - characteristic point zero represents the corresponding point at the beginning of curing (t=0), characteristic point one represents the corresponding point of the peak value of conductivity, characteristic point two represents the curve inflection point (the second-order derivative is 0), and characteristic point three represents the corresponding point at the end of curing; on the conductivity-time curve, the conductivity corresponding to characteristic point zero to characteristic point three is recorded as σ0, σ1, σ2 and σ3, respectively, and the curve segment area from characteristic point one to characteristic point two is recorded as S 12 , the area of the curve segment from feature point 1 to feature point 3 is recorded as S 13 . After calculation, σ1-σ0=39.3-30=9.3mS / m, S 13 / S 12 =134 / 28=4.8.
[0170] The ion dissolution rate of solid waste-based cementitious materials was evaluated as “low” using the value of σ1-σ0, and the ion dissolution rate of solid waste-based cementitious materials was evaluated as “low” using the value of S 13 / S 12 The value of α / α-activated carbonyl chloride was used to evaluate the polymerization degree of the alkali-activated products of the solid waste-based cementitious material as “low”; based on the evaluation results of the ion dissolution rate and the polymerization degree of the alkali-activated products, it was determined that the alkali-activated activity of the solid waste-based cementitious material at 35°C was “low”, and the ceramic powder did not have alkali-activated activity and was not worth using as a solid waste-based cementitious material.
[0171] Example 5
[0172] This embodiment provides a method for evaluating the suitability of solid waste-based cementitious materials, comprising the following steps:
[0173] S1, mixing slag with 10wt% sodium hydroxide aqueous solution, the mass ratio of slag powder to sodium hydroxide aqueous solution is 100:45, pouring into the conductivity test mold 1, vibrating and compacting to obtain a pure slurry specimen.
[0174] S2, put the conductivity test mold 1 into the curing box at 20℃ and RH=95% for curing, and immediately start testing the real-time conductivity of the clean slurry specimen. The curing time is 7d, and the conductivity-time curve is drawn. Mark 4 characteristic points on the conductivity-time curve - characteristic point zero represents the corresponding point at the beginning of curing (t=0), characteristic point one represents the corresponding point of the peak value of conductivity, characteristic point two represents the curve inflection point (the second-order derivative is 0), and characteristic point three represents the corresponding point at the end of curing; on the conductivity-time curve, the conductivity corresponding to characteristic point zero to characteristic point three is recorded as σ0, σ1, σ2 and σ3 respectively, and the curve segment area from characteristic point one to characteristic point two is recorded as S 12 , the area of the curve segment from feature point 1 to feature point 3 is recorded as S 13 . After calculation, σ1-σ0=126-30=96mS / m, S 13 / S 12 =34 / 19=1.8.
[0175] The ion dissolution rate of solid waste-based cementitious materials was evaluated as “high” using the value of σ1-σ0, and the ion dissolution rate of solid waste-based cementitious materials was evaluated as “high” using the value of S 13 / S 12 The value of was used to evaluate the degree of polymerization of the alkali-activated products of the solid waste-based gelling material as “high”; based on the evaluation results of the ion dissolution rate and the degree of polymerization of the alkali-activated products, the alkali-activated activity of the solid waste-based gelling material was determined to be “high”.
[0176] S3, screw the conductivity test mold into the sealed container 2, turn on the vacuum pump 3 to make the air pressure of the sealed container 2 0.2 standard atmospheric pressure, and a solution will precipitate at the filter 11; keep the vacuum condition unchanged, and after no solution precipitates within 10 minutes, test the conductivity σ of the precipitate in the groove 22 p , after calculating σ3 / σ p =8.2×10 -3 / 94=0.87×10 -4 . Using σ3 / σ p The value of evaluates the ion transport resistance of solid waste-based cementitious materials under humid conditions as “high”.
[0177] S4, after completing the test of ion transmission resistance under humid conditions, test the real-time air pressure of the sealed container 2 (ensure that the air pressure of the sealed container 2 is 0.2 standard atmospheres when the test starts). When the air pressure of the closed environment is greater than 0.9 standard atmospheres, stop measuring the real-time air pressure and draw an air pressure-time curve.
[0178] Then, the air pressure-time curve was fitted using Formula 1, and k = 0.011 was obtained. The k value was used to evaluate the gas transmission resistance of the solid waste-based cementitious material under dry conditions as "high".
[0179] p=0.9-0.7e -ktFormula 1
[0180] In formula 1, p represents air pressure, the unit is atm; t represents time, the unit is min; k represents a constant.
[0181] S5. Based on the evaluation results of alkali activation activity, ion transmission resistance under humid conditions, and gas transmission resistance under dry conditions, the application occasion of the solid waste material is determined to be "quick repair".
[0182] Example 6
[0183] This embodiment provides a method for evaluating the suitability of solid waste-based cementitious materials, comprising the following steps:
[0184] S1, mix steel slag, slag and 10wt% sodium hydroxide aqueous solution, the mass ratio of steel slag, steel slag powder and sodium hydroxide aqueous solution is 40:60:45, pour into the conductivity test mold 1, vibrate and compact to obtain a pure slurry specimen.
[0185] S2, put the conductivity test mold 1 into the curing box at 20℃ and RH=95% for curing, and immediately start testing the real-time conductivity of the clean slurry specimen. The curing time is 7d, and the conductivity-time curve is drawn. Mark 4 characteristic points on the conductivity-time curve - characteristic point zero represents the corresponding point at the beginning of curing (t=0), characteristic point one represents the corresponding point of the peak value of conductivity, characteristic point two represents the curve inflection point (the second-order derivative is 0), and characteristic point three represents the corresponding point at the end of curing; on the conductivity-time curve, the conductivity corresponding to characteristic point zero to characteristic point three is recorded as σ0, σ1, σ2 and σ3 respectively, and the curve segment area from characteristic point one to characteristic point two is recorded as S 12 , the area of the curve segment from feature point 1 to feature point 3 is recorded as S 13 . After calculation, σ1-σ0=107-30=77mS / m, S 13 / S 12 =51 / 24.4=2.1.
[0186] The ion dissolution rate of solid waste-based cementitious materials was evaluated as “high” using the value of σ1-σ0, and the ion dissolution rate of solid waste-based cementitious materials was evaluated as “high” using the value of S 13 / S 12 The value of was used to evaluate the degree of polymerization of the alkali-activated products of the solid waste-based gelling material as “high”; based on the evaluation results of the ion dissolution rate and the degree of polymerization of the alkali-activated products, the alkali-activated activity of the solid waste-based gelling material was determined to be “high”.
[0187] S3, screw the conductivity test mold into the sealed container 2, turn on the vacuum pump 3 to make the air pressure of the sealed container 2 0.2 standard atmospheric pressure, and a solution will precipitate at the filter 11; keep the vacuum condition unchanged, and after no solution precipitates within 10 minutes, test the conductivity σ of the precipitate in the groove 22 p, after calculating σ3 / σ p =15×10 -3 / 158=0.95×10 -4 . Using σ3 / σ p The value of evaluates the ion transport resistance of solid waste-based cementitious materials under humid conditions as “high”.
[0188] S4, after completing the test of ion transmission resistance under humid conditions, test the real-time air pressure of the sealed container 2 (ensure that the air pressure of the sealed container 2 is 0.2 standard atmospheres when the test starts). When the air pressure in the closed environment is greater than 0.9 standard atmospheres, stop measuring the real-time air pressure, draw the air pressure-time curve, and then use Formula 1 to fit the air pressure-time curve, and get k=0.022. The k value is used to evaluate the gas transmission resistance of the solid waste-based cementitious material under dry conditions as "medium".
[0189] p=0.9-0.7e -kt Formula 1
[0190] In formula 1, p represents air pressure, the unit is atm; t represents time, the unit is min; k represents a constant.
[0191] S5. Based on the evaluation results of alkali activation activity, ion transmission resistance under humid conditions and gas transmission resistance under dry conditions, the application of solid waste materials is determined to be "rapid repair with frequent contact with water".
[0192] Example 7
[0193] This embodiment provides a method for evaluating the suitability of solid waste-based cementitious materials, comprising the following steps:
[0194] S1, mixing sintered clay brick powder, ceramic powder and 10wt% sodium hydroxide aqueous solution, the mass ratio of sintered clay brick powder, ceramic powder and sodium hydroxide aqueous solution is 70:30:39, pouring into the conductivity test mold 1, vibrating and compacting to obtain a pure slurry specimen.
[0195] S2, put the conductivity test mold 1 into the curing box at 65℃ and RH=95% for curing, and immediately start testing the real-time conductivity of the clean slurry specimen. The curing time is 6.5d, and the conductivity-time curve is drawn. Mark 4 characteristic points on the conductivity-time curve - characteristic point zero represents the corresponding point at the beginning of curing (t=0), characteristic point one represents the corresponding point of the peak value of conductivity, characteristic point two represents the curve inflection point (the second-order derivative is 0), and characteristic point three represents the corresponding point at the end of curing; on the conductivity-time curve, the conductivity corresponding to characteristic point zero to characteristic point three is recorded as σ0, σ1, σ2 and σ3 respectively, and the curve segment area from characteristic point one to characteristic point two is recorded as S 12 , the area of the curve segment from feature point 1 to feature point 3 is recorded as S 13. After calculation, σ1-σ0=85-30=55mS / m, S 13 / S 12 =101 / 39=2.6.
[0196] The ion dissolution rate of solid waste-based cementitious materials was evaluated as “medium” using the value of σ1-σ0, and S 13 / S 12 The value of was used to evaluate the degree of polymerization of the alkali-activated products of the solid waste-based gelling material as “medium”; based on the evaluation results of the ion dissolution rate and the degree of polymerization of the alkali-activated products, the alkali-activated activity of the solid waste-based gelling material was determined to be “medium”.
[0197] S3, screw the conductivity test mold into the sealed container 2, turn on the vacuum pump 3 to make the air pressure of the sealed container 2 0.2 standard atmospheric pressure, and a solution will precipitate at the filter 11; keep the vacuum condition unchanged, and after no solution precipitates within 10 minutes, test the conductivity σ of the precipitate in the groove 22 p , after calculating σ3 / σ p =18.1×10 -3 / 165=1.1×10 -4 . Using σ3 / σ p The value of is used to evaluate the ion transport resistance of solid waste-based cementitious materials under wet conditions as “medium”.
[0198] S4, after completing the test of ion transmission resistance under humid conditions, test the real-time air pressure of the sealed container 2 (ensure that the air pressure of the sealed container 2 is 0.2 standard atmospheres when the test starts). When the air pressure of the closed environment is greater than 0.9 standard atmospheres, stop measuring the real-time air pressure and draw an air pressure-time curve.
[0199] Then, the air pressure-time curve was fitted using Formula 1, and k = 0.017 was obtained. The k value was used to evaluate the gas transmission resistance of the solid waste-based cementitious material under dry conditions as "high".
[0200] p=0.9-0.7e -kt Formula 1
[0201] In formula 1, p represents air pressure, the unit is atm; t represents time, the unit is min; k represents a constant.
[0202] S5. Based on the evaluation results of alkali excitation activity, ion transmission resistance under humid conditions and gas transmission resistance under dry conditions, the application occasion of the solid waste material is determined to be "prefabricated components in dry environments".
[0203] Example 8
[0204] This embodiment provides a method for evaluating the suitability of solid waste-based cementitious materials, comprising the following steps:
[0205] S1, mixing sintered clay brick powder, ceramic powder and 10wt% sodium hydroxide aqueous solution, the mass ratio of sintered clay brick powder, ceramic powder and sodium hydroxide aqueous solution is 50:50:39, pouring into the conductivity test mold 1, vibrating and compacting to obtain a pure slurry specimen.
[0206] S2, put the conductivity test mold 1 into the curing box at 60℃ and RH=95% for curing, and immediately start testing the real-time conductivity of the clean slurry specimen. The curing time is 7d, and the conductivity-time curve is drawn. Mark 4 characteristic points on the conductivity-time curve - characteristic point zero represents the corresponding point at the beginning of curing (t=0), characteristic point one represents the corresponding point of the peak value of conductivity, characteristic point two represents the curve inflection point (the second-order derivative is 0), and characteristic point three represents the corresponding point at the end of curing; on the conductivity-time curve, the conductivity corresponding to characteristic point zero to characteristic point three is recorded as σ0, σ1, σ2 and σ3, respectively, and the curve segment area from characteristic point one to characteristic point two is recorded as S 12 , the area of the curve segment from feature point 1 to feature point 3 is recorded as S 13 . After calculation, σ1-σ0=84-30=54mS / m, S 13 / S 12 =98.5 / 37.81=2.6.
[0207] The ion dissolution rate of solid waste-based cementitious materials was evaluated as “medium” using the value of σ1-σ0, and S 13 / S 12 The value of was used to evaluate the degree of polymerization of the alkali-activated products of the solid waste-based gelling material as “medium”; based on the evaluation results of the ion dissolution rate and the degree of polymerization of the alkali-activated products, the alkali-activated activity of the solid waste-based gelling material was determined to be “medium”.
[0208] S3, screw the conductivity test mold into the sealed container 2, turn on the vacuum pump 3 to make the air pressure of the sealed container 2 0.2 standard atmospheric pressure, and a solution will precipitate at the filter 11; keep the vacuum condition unchanged, and after no solution precipitates within 10 minutes, test the conductivity σ of the precipitate in the groove 22 p , after calculating σ3 / σ p =12.1×10 -3 / 57.62=2.1×10 -4 . Using σ3 / σ p The value of is used to evaluate the ion transport resistance of solid waste-based cementitious materials under wet conditions as “medium”.
[0209] S4, after completing the test of ion transmission resistance under humid conditions, test the real-time air pressure of the sealed container 2 (ensure that the air pressure of the sealed container 2 is 0.2 standard atmospheres when the test starts). When the air pressure of the closed environment is greater than 0.9 standard atmospheres, stop measuring the real-time air pressure and draw an air pressure-time curve.
[0210] Then, the air pressure-time curve was fitted using Formula 1, and k = 0.051 was obtained. The k value was used to evaluate the gas transmission resistance of the solid waste-based cementitious material under dry conditions as "medium".
[0211] p=0.9-0.7e -kt Formula 1
[0212] In formula 1, p represents air pressure, the unit is atm; t represents time, the unit is min; k represents a constant.
[0213] S5. Based on the evaluation results of alkali excitation activity, ion transmission resistance under humid conditions and gas transmission resistance under dry conditions, the application of solid waste materials is determined to be "prefabricated components with a waterproof coating or an anti-corrosion coating on the surface."
[0214] Example 9
[0215] This embodiment provides a method for evaluating the suitability of solid waste-based cementitious materials, comprising the following steps:
[0216] S1, mixing slag, ceramic powder and 10wt% sodium hydroxide aqueous solution, the mass ratio of slag, ceramic powder and sodium hydroxide aqueous solution is 55:45:39, pouring into the conductivity test mold 1, vibrating and compacting to obtain a pure slurry specimen.
[0217] S2, put the conductivity test mold 1 into the curing box at 30℃ and RH=95% for curing, and immediately start testing the real-time conductivity of the clean slurry specimen. The curing time is 7d, and the conductivity-time curve is drawn. Mark 4 characteristic points on the conductivity-time curve - characteristic point zero represents the corresponding point at the beginning of curing (t=0), characteristic point one represents the corresponding point of the peak value of conductivity, characteristic point two represents the curve inflection point (the second-order derivative is 0), and characteristic point three represents the corresponding point at the end of curing; on the conductivity-time curve, the conductivity corresponding to characteristic point zero to characteristic point three is recorded as σ0, σ1, σ2 and σ3, respectively, and the curve segment area from characteristic point one to characteristic point two is recorded as S 12 , the area of the curve segment from feature point 1 to feature point 3 is recorded as S 13 . After calculation, σ1-σ0=106-30=76mS / m, S 13 / S 12 =62.1 / 31.06=2.0.
[0218] The ion dissolution rate of solid waste-based cementitious materials was evaluated as “high” using the value of σ1-σ0, and the ion dissolution rate of solid waste-based cementitious materials was evaluated as “high” using the value of S 13 / S 12The value of was used to evaluate the degree of polymerization of the alkali-activated products of the solid waste-based gelling material as “high”; based on the evaluation results of the ion dissolution rate and the degree of polymerization of the alkali-activated products, the alkali-activated activity of the solid waste-based gelling material was determined to be “high”.
[0219] S3, screw the conductivity test mold into the sealed container 2, turn on the vacuum pump 3 to make the air pressure of the sealed container 2 0.2 standard atmospheric pressure, and a solution will precipitate at the filter 11; keep the vacuum condition unchanged, and after no solution precipitates within 10 minutes, test the conductivity σ of the precipitate in the groove 22 p , after calculating σ3 / σ p =11.6×10 -3 / 50.26=2.3×10 -4 . Using σ3 / σ p The value of is used to evaluate the ion transport resistance of solid waste-based cementitious materials under wet conditions as “medium”.
[0220] S4, after completing the test of ion transmission resistance under humid conditions, test the real-time air pressure of the sealed container 2 (ensure that the air pressure of the sealed container 2 is 0.2 standard atmospheres when the test starts). When the air pressure of the closed environment is greater than 0.9 standard atmospheres, stop measuring the real-time air pressure and draw an air pressure-time curve.
[0221] Then, the air pressure-time curve was fitted using Formula 1, and k = 0.049 was obtained. The k value was used to evaluate the gas transmission resistance of the solid waste-based cementitious material under dry conditions as "medium".
[0222] p=0.9-0.7e -kt Formula 1
[0223] In formula 1, p represents air pressure, the unit is atm; t represents time, the unit is min; k represents a constant.
[0224] S5. Based on the evaluation results of alkali excitation activity, ion transmission resistance under humid conditions and gas transmission resistance under dry conditions, the application scenarios of solid waste materials are determined to be "cast-in-place components with waterproof coating or anti-corrosion coating on the surface".
[0225] Application Example 1
[0226] This application example provides a concrete made from the solid waste materials in Example 1, which is composed of the following raw materials in parts by weight: 200 parts of steel slag, 200 parts of ceramic powder, 160 parts of 10wt% water glass solution, 800 parts of sand and 1060 parts of gravel.
[0227] The method for preparing the concrete comprises the following steps:
[0228] Weigh all raw materials according to the designed proportion, mix them evenly, place them in a cubic mold with a side length of 100 mm, and perform standard curing for 3 days to obtain concrete.
[0229] According to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 3d compressive strength of the concrete in this application example was tested by a pressure testing machine and was 47MPa. The concrete was placed in indoor air for 6 months, and no efflorescence phenomenon appeared on its surface. The chloride ion migration coefficient (D RCM ) is 3.15×10 -12 m 2 / s. Figg permeability index (FPI) is 312s.
[0230] Application Example 2
[0231] This application example provides a concrete made from the solid waste materials in Example 2, which is composed of the following raw materials in parts by weight: 320 parts of steel slag, 80 parts of ceramic powder, 160 parts of 10wt% water glass solution, 800 parts of sand and 1060 parts of gravel.
[0232] The preparation method of the above concrete is the same as that of Application Example 1 and will not be described in detail.
[0233] According to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 3d compressive strength of concrete in this application example was tested by a pressure testing machine and was 31MPa. The average depth of chloride ion penetration obtained by RCM test was less than 8mm. After calculation, the chloride ion migration coefficient (D RCM ) is 1.86×10 -12 m 2 / s. Figg permeability index (FPI) is 271s.
[0234] Application Example 3
[0235] This application example provides a concrete made from the solid waste materials in Example 3, which is composed of the following raw materials in parts by weight: 400 parts of sintered clay bricks, 160 parts of 10wt% water glass solution, 800 parts of sand and 1060 parts of gravel.
[0236] The method for preparing the concrete comprises the following steps:
[0237] Weigh all raw materials according to the designed proportion, mix them evenly, place them in a cubic mold with a side length of 100 mm, and cure at 60°C for 3 days to obtain concrete.
[0238] According to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 3d compressive strength of the concrete in this application example was tested by a pressure testing machine and was 54MPa. The chloride ion migration coefficient (D RCM ) is 1.77×10 -12 m 2 / s. Figg permeability index (FPI) is 386s.
[0239] Application Example 4
[0240] This application example provides a concrete made from the solid waste materials in Example 4, which is composed of the following raw materials in parts by weight: 400 parts of ceramic powder, 160 parts of 10wt% water glass solution, 800 parts of sand and 1060 parts of gravel.
[0241] The preparation method of the above concrete is the same as that of Application Example 1 and will not be described in detail.
[0242] The concrete still cannot harden after 3 days, so it is impossible to carry out compressive strength test, chloride ion migration coefficient test and gas transmission resistance test.
[0243] Application Example 5
[0244] This application example provides a concrete made from the solid waste materials in Example 5, which is composed of the following raw materials in parts by weight: 400 parts of slag powder, 160 parts of 10wt% water glass solution, 800 parts of sand and 1060 parts of gravel.
[0245] The preparation method of the above concrete is the same as that of Application Example 1 and will not be described in detail.
[0246] According to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 3d compressive strength of the concrete in this application example was tested by a pressure testing machine and was 68MPa. The chloride ion migration coefficient (D RCM ) is 1.58×10 -12 m 2 / s. Figg permeability index (FPI) is 405s.
[0247] Application Example 6
[0248] This application example provides a concrete made from the solid waste materials in Example 6, which is composed of the following raw materials in parts by weight: 160 parts of steel slag, 240 parts of slag powder, 160 parts of 10wt% water glass solution, 800 parts of sand and 1060 parts of gravel.
[0249] The preparation method of the above concrete is the same as that of Application Example 1 and will not be described in detail.
[0250] According to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 3d compressive strength of concrete in this application example was tested by a pressure testing machine and was 47MPa. The chloride ion migration coefficient (D RCM ) is 1.81×10 -12 m 2 / s. Figg permeability index (FPI) is 281s.
[0251] Application Example 7
[0252] This application example provides a concrete made from the solid waste materials in Example 7, which is composed of the following raw materials in parts by weight: 280 parts of sintered clay brick powder, 120 parts of ceramic powder, 160 parts of 10wt% water glass solution, 800 parts of sand and 1060 parts of gravel.
[0253] The preparation method of the above concrete is the same as that of Application Example 3 and will not be described in detail.
[0254] According to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 3d compressive strength of the concrete in this application example was tested by a pressure testing machine and was 38MPa. The concrete was placed in indoor air for 6 months, and no efflorescence phenomenon appeared on its surface. The chloride ion migration coefficient (D RCM ) is 2.01×10 -12 m 2 / s. Figg permeability index (FPI) is 395s.
[0255] Application Example 8
[0256] This application example provides a concrete made from the solid waste materials in Example 8, which is composed of the following raw materials in parts by weight: 200 parts of sintered clay brick powder, 200 parts of ceramic powder, 160 parts of 10wt% water glass solution, 800 parts of sand and 1060 parts of gravel.
[0257] The preparation method of the above concrete is the same as that of Application Example 3 and will not be described in detail.
[0258] According to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 3d compressive strength of concrete in this application example was tested by a pressure testing machine and was 34MPa. The chloride ion migration coefficient (D RCM ) is 4.13×10 -12 m 2 / s. Figg permeability index (FPI) is 71s.
[0259] Application Example 9
[0260] This application example provides a concrete made from the solid waste materials in Example 9, which is composed of the following raw materials in parts by weight: 220 parts of slag, 180 parts of ceramic powder, 160 parts of 10wt% water glass solution, 800 parts of sand and 1060 parts of gravel.
[0261] The method for preparing the concrete comprises the following steps:
[0262] Weigh all raw materials according to the designed proportion, mix them evenly, place them in a cubic mold with a side length of 100 mm, and cure at 30°C for 3 days to obtain concrete.
[0263] According to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 3d compressive strength of the concrete in this application example was tested by a pressure testing machine and was 50.4MPa. The chloride ion migration coefficient (D RCM ) is 4.53×10 -12 m 2 / s. Figg permeability index (FPI) is 82s.
[0264] Verification test
[0265] The present invention is compared with related test methods to verify the accuracy of the applicability evaluation method for solid waste-based cementitious materials provided by the present invention.
[0266] 1. According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", a pressure testing machine was used to test the 3d compressive strength of concrete in the application example to verify the accuracy of the evaluation of the alkali-activated activity of the solid waste-based cementitious materials used. The test results are as follows: Figure 11~Figure 12 shown. Figure 11~Figure 12 The point where the compressive strength is 0 means that the mixture has not hardened and the compressive strength test cannot be carried out.
[0267] 2. According to GB / T 50082-2024 "Standard for Test Methods for Long-term Performance and Durability of Concrete", the non-steady-state chloride ion migration test (also known as RCM method) was used to test the chloride ion migration coefficient of the concrete in the application example to verify the accuracy of the evaluation of the ion transport resistance of the solid waste-based cementitious materials used under humid working conditions. The test results are as follows: Fig.13 It should be noted that since some mixtures cannot be hardened, RCM tests cannot be carried out. Fig.13 The corresponding points are not included.
[0268] Luping TANG of Chalmers University of Technology in Sweden, the originator of the RCM method, believes that the evaluation criteria for ion transport resistance expressed by chloride ion migration coefficient are shown in Table 1.
[0269] Table 1
[0270]
[0271] 3. The Figg (pressure difference change) gas permeability test was used to verify the accuracy of the evaluation of the gas transmission resistance of the solid waste-based cementitious materials used in the corresponding case under dry conditions according to the official method (see Figg, JW Methods of measuring the air and water permeability of concrete. Magazine of Concrete Research, 1973, 25(85): 213-291.). The test results are as follows: Fig.14 shown.
[0272] Among them, the relationship between Figg permeability index (FPI) and concrete gas transmission resistance classification is shown in Table 2 (see "The testing of concrete in structures", Bungey JH, published by Blackie and Son Ltd, New York).
[0273] Table 2
[0274] Gas transmission resistance classification high medium Low FPI >300s 100s~300s <100s
[0275] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for evaluating the suitability of solid waste-based cementitious materials, characterized in that: The following steps are involved: S1, mixing the solid waste material with the alkaline stimulating solution to obtain a pure slurry specimen; S2, curing the clean slurry specimen, testing the real-time conductivity, and drawing a conductivity-time curve; and then evaluating the alkali activation activity of the solid waste-based gelling material according to the information of the conductivity-time curve; The specific steps of evaluating the alkali-activated activity of the solid waste-based gelling material according to the information of the conductivity-time curve include: Four characteristic points are marked on the conductivity-time curve: characteristic point zero represents the corresponding point at the beginning of the curing, characteristic point one represents the corresponding point at the peak value of the conductivity, characteristic point two represents the curve inflection point, and characteristic point three represents the corresponding point at the end of the curing; wherein the curve inflection point represents the point where the second-order derivative is 0; On the conductivity-time curve, the conductivities corresponding to the characteristic points 0 to 3 are denoted as σ0, σ1, σ2 and σ3 respectively, and the area formed by the curve segment from the characteristic point 1 to the characteristic point 2 and the horizontal coordinate is denoted as S 12 The area formed by the curve segment from feature point 1 to feature point 3 and the horizontal coordinate is recorded as S 13 ; The ion dissolution rate of the solid waste-based cementitious material is evaluated by using the value of σ1-σ0, and the ion dissolution rate of the solid waste-based cementitious material is evaluated by using S 13 / S 12 The value of is used to evaluate the degree of polymerization of the alkali-activated product of the solid waste-based gelling material; and the alkali-activated activity of the solid waste-based gelling material is determined according to the evaluation results of the ion dissolution rate and the degree of polymerization of the alkali-activated product. S3, under vacuum conditions, allowing the cured clean slurry specimen to precipitate a solution, and testing the conductivity of the precipitated solution to evaluate the ion transport resistance of the solid waste-based gelling material under humid conditions; S4, placing the clean slurry specimen after the solution is precipitated into a closed environment with a pressure of ≤-80 kPa, and testing the real-time air pressure to draw an air pressure-time curve; then fitting the air pressure-time curve using formula 1 to obtain a k value, and using the k value to evaluate the gas transmission resistance of the solid waste-based cementitious material under dry conditions; p=0.9-0.7e -kt Formula 1 In formula 1, p represents air pressure in atm; t represents time in min; k represents a constant; S5, determining application scenarios of the solid waste material according to the evaluation results of the alkali excitation activity, the ion transmission resistance under wet conditions, and the gas transmission resistance under dry conditions.
2. The method for evaluating the suitability of solid waste-based cementitious materials according to claim 1, characterized in that: In S3, the conductivity of the precipitate is denoted as σ p , using σ3 / σ p The value of is used to evaluate the ion transport resistance of the solid waste-based cementitious material under humid conditions.
3. The method for evaluating the suitability of solid waste-based cementitious materials according to claim 2, characterized in that: In S2, the criteria for evaluating the ion dissolution rate of the solid waste-based cementitious material using the values of σ1-σ0 include: When σ1-σ0>60mS / m, the evaluation result is that the ion dissolution rate is high; When σ1-σ0=30mS / m~60mS / m, the evaluation result is medium ion dissolution rate; When σ1-σ0<30mS / m, the evaluation result is that the ion dissolution rate is low; In S2, S 13 / S 12 The criteria for evaluating the degree of polymerization of the alkali-activated product of the solid waste-based cementitious material include: When S 13 / S 12 When <2.2, the evaluation result is that the degree of polymerization is high; When S 13 / S 12 =2.2~4, the evaluation result is medium degree of polymerization; When S 13 / S 12 When >4, the evaluation result is that the degree of polymerization is low; In S2, the criteria for determining the alkali-activated activity of the solid waste-based gelling material include: When the evaluation result of the ion dissolution rate is that the ion dissolution rate is high, and the evaluation result of the degree of polymerization of the base-excited product is that the degree of polymerization is high, the evaluation result of the base-excited activity is that the base-excited activity is high; When the evaluation result of the ion dissolution rate is high, and the evaluation result of the degree of polymerization of the base-excited product is medium, the evaluation result of the base-excited activity is medium; When the evaluation result of the ion dissolution rate is medium, and the evaluation result of the degree of polymerization of the base-excited product is high, the evaluation result of the base-excited activity is medium; When the evaluation result of the ion dissolution rate is medium, and the evaluation result of the degree of polymerization of the base-excited product is medium, the evaluation result of the base-excited activity is medium; As long as the evaluation result of the ion dissolution rate or the degree of polymerization of the alkali-activated product shows "low", the solid waste material does not have alkali-activated activity and has no value for use as a solid waste-based gelling material; In S3, σ3 / σ is used p The criteria for evaluating the ion transport resistance of the solid waste-based cementitious material under humid working conditions include: When σ3 / σ p <10 -4 When , the evaluation result is that the ion transmission resistance is high; When σ3 / σ p =1×10 -4 ~3×10 -4 When , the evaluation result is that the ion transmission resistance is medium; When σ3 / σ p >3×10 -4 When , the evaluation result is that the ion transmission resistance is low; In S4, the criteria for evaluating the gas transmission resistance of the solid waste-based cementitious material under dry conditions using the k value include: When k < 0.02, the evaluation result is that the gas transmission resistance is high; When k = 0.02 ~ 0.06, the evaluation result is medium gas transmission resistance; When k>0.06, the evaluation result is that the gas transmission resistance is low.
4. The method for evaluating the suitability of solid waste-based cementitious materials according to claim 3, characterized in that: In S5, the criteria for determining the application of the solid waste material include: When the evaluation result of the alkali excitation activity is high alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is high ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is high gas transmission resistance, the application occasion of the solid waste material is a rapid repair occasion; When the evaluation result of the alkali excitation activity is high alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is high ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is medium gas transmission resistance, the application occasion of the solid waste material is a rapid repair occasion that is often in contact with water; When the evaluation result of the alkali excitation activity is high alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is medium ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is high gas transmission resistance, the application occasion of the solid waste material is a rapid repair occasion in a dry environment; When the evaluation result of the alkali excitation activity is high alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based cementitious material under wet conditions is medium ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based cementitious material under dry conditions is medium gas transmission resistance, the application occasion of the solid waste material is a cast-in-place component with a waterproof coating or an anti-corrosion coating on the surface; When the evaluation result of the alkali excitation activity is medium alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is high ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is high gas transmission resistance, the application occasion of the solid waste material is prefabricated component occasion; When the evaluation result of the alkali excitation activity is medium alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is medium ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is high gas transmission resistance, the application occasion of the solid waste material is a prefabricated component occasion in a dry environment; When the evaluation result of the alkali excitation activity is medium alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is high ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is medium gas transmission resistance, the application occasion of the solid waste material is a prefabricated component occasion that is often in contact with water; When the evaluation result of the alkali excitation activity is medium alkali excitation activity, the evaluation result of the ion transmission resistance of the solid waste-based gelling material under wet conditions is medium ion transmission resistance, and the evaluation result of the gas transmission resistance of the solid waste-based gelling material under dry conditions is medium gas transmission resistance, the application occasion of the solid waste material is a prefabricated component with a waterproof coating or an anti-corrosion coating on the surface; As long as "low" appears in the evaluation results of the alkali activation activity, the ion transport resistance under wet conditions, or the gas transport resistance under dry conditions, the solid waste material has no value for use as a solid waste-based gelling material.
5. The method for evaluating the suitability of solid waste-based cementitious materials according to claim 1, characterized in that: In S1, the solid waste material includes aluminosilicate solid waste material; In S1, the alkaline excitation solution includes at least one of a sodium hydroxide aqueous solution, a sodium silicate aqueous solution, a potassium hydroxide aqueous solution or a sodium carbonate aqueous solution; In S1, the mass concentration of the alkaline excitation solution is 8% to 15%; In S1, the mass ratio of the solid waste material to the alkaline excitation solution is 100:(35~45).
6. The method for evaluating the suitability of solid waste-based cementitious materials according to claim 1 or 5, characterized in that: In S1, the solid waste material includes at least one of steel slag, ceramics, sintered clay bricks or slag; In S2, the curing temperature is 20°C to 65°C, the relative humidity is ≥ 90%, and the curing time is 6d to 9d; In S3, the vacuum pressure is ≤-80 kPa; In S4, when the air pressure of the closed environment is ≥-10 kPa, the measurement of the real-time air pressure is stopped.
7. A system for evaluating the suitability of solid waste-based cementitious materials, characterized in that: The method comprises a conductivity test mold and a closed container, and is used for evaluating the applicability of solid waste-based cementitious materials according to any one of claims 1 to 6; wherein: The conductivity test mold is located in the upper middle part of the closed container and is used to place the clean slurry specimen and perform real-time conductivity test on the clean slurry specimen during the curing process; An opening having the same size as the periphery of the conductivity test mold is provided in the middle and upper part of the sealed container for placing the conductivity test mold; The sealed container is connected with a vacuum pump for constructing a vacuum environment and a sealed environment, so that the clean slurry specimen after curing precipitates a solution, and a real-time air pressure test is performed on the clean slurry specimen after the solution is precipitated; A filter screen is provided at the bottom of the conductivity test mold for dripping the precipitate; A groove is provided at the bottom of the sealed container, and the groove is located directly below the filter screen, and is used to hold the precipitate and test the conductivity of the precipitate.
8. The system for evaluating the suitability of solid waste-based cementitious materials according to claim 7, characterized in that: The upper part of the conductivity test mold is a hollow cylinder, the outer side of the cylinder is provided with threads, and the opening of the sealed container corresponding to the outer side of the cylinder is also provided with threads, and the conductivity test mold and the sealed container are screwed together through the threads; The lower part of the conductivity test mold is a hollow funnel-shaped cone, and the bottom of the funnel-shaped cone is the filter screen.
9. The suitability evaluation system for solid waste-based cementitious materials according to claim 8, characterized in that: Two layers of parallel platinum mesh are arranged inside the cylinder, the diameter of the platinum mesh is the same as the inner diameter of the cylinder, the clean slurry specimen is placed between the two layers of platinum mesh, and the two layers of platinum mesh are respectively connected to the conductivity tester through leads; The spacing between the two layers of the platinum mesh is 20 mm to 30 mm, and the diameter of the platinum mesh is 50 mm to 80 mm; the mesh of the platinum mesh is a square with a side length of 1 mm to 3 mm, and the diameter of the platinum wire is 0.2 mm to 0.5 mm; The diameter of the filter is 1 cm to 2 cm, and the mesh size of the filter is ≤ 0.5 mm; The volume of the sealed container is 800mL~1000mL.
Citation Information
Patent Citations
Method and system for non-contact electrical resistivity-based evaluation of permeability of cement-based material
CN103267719A
Long-acting evaluation method for active magnesium oxide solidified / stabilized zinc-containing smelting slag based on carbonation accelerated exposure
CN114428149A